Аналіз існуючих методів дослідження впливу автомобільного транспорту на довкілля - Коник, Ігор; Масьонков, Олег; Вовк, Юлія (Посвіт, 2019)
In this paper the methods of calculation of emissions of harmful substances into the environment by motor transport flows are given. Also, possible methods for improving these techniques with the help of additional calculations are given.
Analysis of existing methods of the investigation of the impact of automotive transport on the environment
Keywords: 656.13